FOURIER TRANSFORM INFRARED ANALYSIS OF ULVA LACTUCA AND GRACILARIA CORTICATA AND THEIR EFFECT ON ANTIBACTERIAL ACTIVITY - RADHIKA D; A, Mohaideen (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â In the present work, we used two seaweeds Ulva lactuca and Gracilaria corticata, which were collected from Hare Island in the Gulf of Mannar of Tuticorin coast. Ethanol was taken as the solvent for extraction. The crude extract was purified using column chromatography. Antibacterial activity of crude and column purified fractions were tested against Klebsiella, Aeromonas, Staphylococcus, Escherichia and Pseudomonas using well-diffusion method. Maximum zone of inhibition (9 mm) was found in the crude extract of G. corticata against Pseudomonas sp. Minimum zone of inhibition (4 mm) was found in U. lactuca fraction1 against Escherichia coli. Highest antibacterial activity was obtained in red seaweed, whereas, green seaweed showed less antibacterial activity. From this study, we can conclude that red seaweeds have more active than green seaweeds. The seaweed powder was analyzed in Fourier transform infrared spectrometer. It was observed that both seaweed contained phenol and alcohol compounds, which were responsible for the antibacterial activity. Keywords: Antibacterial activity, Fourier transform infrared, Seaweeds, Ulva lactuca, Gracilaria corticata. Â